Students’ Perception toward Microteaching Class in Relation with Internship Program - Azzahra, Sabrina Dwi; Anugerahwati, Mirjam (Universitas Negeri Malang, 2024)
Microteaching is one of the core courses required by English Language Education students before undertaking an internship program. To be a professional teacher, a teacher must have 4 competencies those are pedagogical competence, personality competence, social competence, and professional competence. Thus, microteaching is needed for students-teachers to help them improve their teaching skills. The purpose of this study is to highlight the students’ perception of microteaching courses on specific topics such as students’ experiences in improving their teaching skills through feedback given by their lecturer and friends, the importance of microteaching for students, and students' need during the process of the microteaching class. The research subjects were 35 undergraduate English Language Education students (2018 cohort) who have taken microteaching courses and internship programs. This research used a qualitative descriptive method using explorative case study. The instruments for the data collection were questionnaires and interviews. The result showed positive attitudes towards the microteaching course. This research discovers the usefulness of microteaching classes in 3 aspects which are enriching students' knowledge before they teach in a real situation in an internship program, improving teaching skills to be implemented in their internship program, and helping students get the basic knowledge from the lecturer for developing lesson plans and learning media. Moreover, it builds student-teachers’ self-confidence and increases teaching skills in peer-teaching.